An interpretation of the concept of knowledge management proposed by Nonaka & Takeuchi using literary fiction - Frías-Navarro, Rosalba; Rodríguez-Romero, Carlos Alberto (Universidad Pedagógica y Tecnológica de Colombia, 2012)
This article aims to present the role of literary fiction -narrative, metaphor and analogy and its expression through rhetorics- in organizational contexts such as the research and practice of management sciences, by using it for the interpretation of the concept of knowledge management proposed by Nonaka y Takeuchi (1995). This information is useful for researchers, both of social and human sciences, as for managers and strategists because they would have the opportunity of exploring the potential that fiction has not only as a “way of entertainment” but as a media of transferring knowledge within organizations.